Pemanfaatan Lingkungan Sekitar sebagai Sumber Belajar IPS di SD - Muhammad Kaulan Karima; Erni, Erni; Annisa Fitria; Annisa Rahayu; Hikmah Apriasih Riswanti; Njuah Mayatih Lumban Gaol; Siti Sundari Jaya Ningrat; Syalinni Kemala Nur; Salsa Islami Pashya (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to explore the use of the surrounding environment as a learning resource in Social Studies (IPS) learning at State Elementary School 2 Metro Timur. The method used is a qualitative approach with a phenomenological research type. Interviews with teachers and students and analysis of supporting documents were used to do this. The results of the study indicate that the surrounding environment, such as school gardens and community social activities, can be used as contextual and meaningful learning resources. Because environment-based learning is considered more interesting and easier to understand, students respond well to it. However, there are several obstacles. These include time constraints, unpredictable weather, poor student coordination, and limited facilities. Teachers must plan well, use alternative learning media, divide clear roles in group activities, and optimize school facilities. According to this study, environment-based IPS learning can create an active, contextual, and relevant learning atmosphere to students' real lives, and has the potential to improve their conceptual understanding and social skills.